ICON 9—an international phase III randomized study to evaluate the efficacy of maintenance therapy with olaparib and cediranib or olaparib alone in patients with relapsed platinum‐sensitive ovarian cancer following a response to platinum‐based chemotherapy. Issue 1 (January 2021) - Elyashiv, Osnat; Ledermann, Jonathan; Parmar, Gita; Farrelly, Laura; Counsell, Nicholas; Feeney, Amanda; El‐Khouly, Fatima; Macdonald, Ian; Neto, Andreia; Arthur‐Darkwa, Esther; Burnett, Eva; Jayson, Gordon C; et al.
Abstract : Background : Two novel biological agents—cediranib targeting angiogenesis, and olaparib targeting DNA repair processes—have individually led to an improvement in ovarian cancer control. The aim of ICON9 is to investigate the combination of cediranib and olaparib maintenance in recurrent ovarian cancer following platinum‐based therapy. Primary objective : To assess the efficacy of maintenance treatment with olaparib in combination with cediranib compared with olaparib alone following a response to platinum‐based chemotherapy in women with platinum‐sensitive ovarian, fallopian tube or peritoneal cancer during first relapse. Study hypothesis : Maintenance therapy with cediranib and olaparib in combination is associated with improved patient outcomes compared with olaparib alone. Trial design : International phase III randomized controlled trial. Following a response to platinum‐based chemotherapy patients are randomized 1:1 to either oral olaparib and cediranib (intervention arm) or oral olaparib alone (control arm). Major inclusion criteria : Patients with a known diagnosis of high grade serous or endometrioid carcinoma of the ovary, fallopian tube or peritoneum, progressing more than 6 months after first‐line platinum‐based chemotherapy, who have responded to second‐line platinum‐based chemotherapy. Primary endpoints : Progression‐free and overall survival. Co‐primary endpoints to be assessed using a fixed‐sequence gatekeeping approach: (1) progression‐free survival, all patients; (2) progression‐free survival, BRCA wild type; (3) overall survival, all patients; (4) overall survival, BRCA wild type. Sample size : 618 patients will be recruited. Estimated dates for completing accrual and presenting results : Accrual is expected to be completed in 2024 with presentation of results in 2025. Trial registration : ClinicalTrials.gov: NCT03278717.